Pelatihan Pembuatan Dokumen Ekspor pada PT Pacific Express Cargo - Widhiastuti, Ni Luh Putu; Srimeliani, Ni Luh (Jurnal Dehasen Mengabdi, 2024)
In export activities, several documents are required to be prepared so that export activities can run smoothly without any obstacles. Some of the export documents required for export activities are Invoice/Packing list, Certificate of Origin, and PEB. PT Pacific Express Cargo is a company operating in the export-import and freight forwarding sector which is located on Jalan Hang Tuah No. 1-3X Denpasar. Errors and delays in the process of making export documents at PT. Pacific Express Cargo occurs frequently, which results in delays in export activities. Therefore, this activity is carried out with the aim of minimizing the occurrence of errors and delays in making export documents. The approach methods used are counseling, training and utilization. The result of this activity is that employees in the export documents section at PT. Pacific Express Cargo is able to make documents well so that errors and delays that occur in making export documents can be minimized and document section employees can work optimally.